(Re)conceptualising the boundaries between home and homelessness: the unheimlich. Issue 6 (18th August 2018) - McCarthy, Lindsey
Abstract: A burgeoning cross-disciplinary literature signifies a move towards diversifying understandings of the meanings of 'home'. Homelessness is inextricably bound up in these definitions. While earlier work has considered meanings of homelessness, attempts to advance understandings of the relationship between home and homelessness have been sporadic. This article attempts to reinvigorate discussion around the home–homelessness relationship by problematizing the binaries in current understandings and poses a different way of theorizing the interplay between the two concepts. Drawing on interviews with women accessing homelessness services in the North of England, discussion interweaves women's meanings of home and homelessness with the Freudian notion of the 'unheimlich'. The 'unheimlich' captures the uncanny process of inversion whereby the familiar domestic sphere of the house turns into a frightening place; and a typical space of homelessness—the hostel—is considered home. The article seeks to contribute more adequate theoretical tools for future research to better understand and articulate the complexities of home and homelessness.